A commentary on Isocrates' Busiris - Livingstone, Niall (Mnemosyne, bibliotheca classica Batava. Supplementum, 2001)
This volume contains a scholarly commentary on the puzzling work "Busiris"--Part mythological "jeu d'esprit", part rhetorical treatise and part self-promoting polemic - by the Greek educator and rhetorician Isocrates (436-338 BC).